The death of expertise the campaign against established knowledge and why it matters - Nichols, Thomas M. 1960- (Oxford University Press, 2024)
Since the original publication of The Death of Expertise, the assault on experts has only ratcheted up. Numerous forces have driven the increase, including a deepening of populist anti-intellectualism, a notable rise in conspiratorial thinking, and the hostile reaction to the medical establishment during the Covid pandemic. Trump and Trumpism, of course, have also played an outsized role, and social media continues to fan the flames. In this new edition, Tom Nichols covers the latest developments in the past half dozen years. Along with updating all the chapters, he has added a chapter on the Covid pandemic. Arguably the most influential book written on the attack on expertise in our era, this new edition is sure to remain the standard book on the subject
Description based on publisher supplied metadata and other sources